Reverse Knowledge Flows: How and When Do Preparation and Reintegration Facilitate Repatriate Knowledge Transfer? - Vesa Peltokorpi; Fabian Jintae Froese; B. Sebastian Reiche; Sebastian Klar (Journal of Management Studies, 2022)
This paper applies a generalized exchange perspective to examine how and when reintegration in headquarters (HQ) facilitates repatriate knowledge transfer (RKT). Specifically, we theorize how the preparatory stage for repatriation – when expatriates are still abroad – enhances reintegration in HQ upon repatriation and subsequently RKT via interpersonal and career-related pathways. For the former, we hypothesize that communication frequency with HQ actors before re-entry enhances RKT via reintegration. We also hypothesize that communication frequency with HQ actors before re-entry improves trust in HQ actors, which, in turn, strengthens the positive effect of reintegration on RKT. For the second pathway, we hypothesize that career and repatriate support before re-entry increases RKT via reintegration. We also hypothesize that career and repatriate support before re-entry enhances career satisfaction upon re-entry, which, in turn, strengthens the positive effect of reintegration on RKT. Time-lagged data from 129 assignees and their HQ supervisors support most of our hypotheses.
Keywords: 650; expatriation; knowledge transfer; reintegration; repatriation; social exchange theory; generalized exchange